The causal effects of expected depreciations - Martha Elena Delgado; Juan Herre\~no; Marc Hofstetter; Mathieu Pedemonte (Inter-American Development Bank (IDB), 2024)
We estimate the causal effects of a shift in the future expected exchange rate of a local currency against the US dollar on a representative sample of firms in a small open economy. We survey a nationally representative sample of firms and provide the one-year-ahead nominal exchange rate forecast published by the local central bank to a random sub-sample of firm managers. This information treatment is effective in shifting exchange rate expectations and perceptions. These effects are persistent and larger for non-exporting firms. Linking survey responses with administrative census data, we estimate a positive elasticity of current import expenditures to a future expected depreciation. Our estimates highlight the intertemporal margin of trade to anticipated changes in trade costs.
Keywords: E31; E71; F31; G41; 330; Expectations; Exchange rate; Firms; Trade